Efektivitas Penggunaan Sabun Smart Clean di Desa Trayu, Kecamatan Sumowono dalam Rangka Pencapaian Sustainable Development Goals - Yuliyani, Dwi Nur; Apriyantika, Merli (Jounal of Enviromental Science Sustainable, 2024)
This study aims to evaluate the effectiveness of the use of Smart Clean soap in Trayu Village, Sumowono District, in supporting the achievement of the Sustainable Development Goals (SDGs), especially goal 6 (clean water and proper sanitation) and goal 12 (responsible consumption and production). Smart Clean soap is a cleaning product designed to reduce environmental impacts through the use of environmentally friendly materials and efficiency in its use. This study uses a survey method with a quantitative and qualitative approach to measure the impact of soap use on cleanliness, public health, and its impact on reducing plastic waste. The results of the study indicate that the use of Smart Clean soap in Trayu Village has a positive contribution to improving sanitation, reducing the use of hazardous chemical products, and increasing public awareness of environmental sustainability.